Multivariate analysis of short and long-impact indicators for corporate bond market development - Astrauskaitė, Ieva (Business, Management and Economics Engineering, 2016)
An additional instrument or established access to the capital market funding would increase business opportunities for performance, development, growth, channeling financing for sustainable and long-term economic growth and job creation. Capital market and its level of development or further development opportunities are exposed to different factors. Clear identification of them mobilizes the attention of accurate and useful decisions or actions influencing the expected results, their adoption and implementation, monitoring. With the purpose to identify a set of factors influencing the capital market deve lopment as well as to introduce a model of their short term and long term impact projections, the ARDL model for the US and Lithuanian cases is introduced. The concluding remarks state on different legal and regulatory framework, banking sector and ICT measures exposures to the different stages of the corporate bond market development.